12 Prinsip Animasi Dalam Film Stopmotion “Shaun The Sheep” - Aditya Nugraha Wibisono Putra; Rizal Yendra Pratama; Rahma Elmira Fairuza (Peneliti.net, 2023)
Animation always has some advantages in various aspects, for example always iconic Japanese animation with visual density and CGI used, then there are Western animations such as Disney, Pixar and so on which are superior with his “Exaggeration” Technique. The application of these 12 animations is mostly used on stopmotion lately like Corpse Bride and Shaun The Sheep The Movie, with hyperbole on some aspects of the 12 Animations made the writer a bit think how the results would be if the 12 aspects were put in level and intensity using the same theory that Ollie Johnston and Frank Thomas wrote about in a book entitled The Illusion of Life: Disney Animation which was written in 1981, namely by reducing some aspects beyond the Application of the 12 Animations, at the same time it will break the deadlock of the Animation Studio working on it the stopmotion. With this analysis, there will be lots of stopmotion animations expected to improvise from the old Stopmotion animation with an emphasis on 12 Principles Animation, both western and local films.